(untitled) (Journal of Partial Differential Equations, 1994)
The initial value problem for a nonlinear evolution system with singular integral differential terms is studied. Dy means of a priori estimates of the solutions and Lcray-Schauder’s fixed point theorem, we demonstrate the existence and uniqueness theorems of the generalized and classical global solutions to the problem.